2022
DOI: 10.1111/psyg.12822
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a multimodal approach to food art therapy on people with mild cognitive impairment and mild dementia

Abstract: Background Food art therapy (FAT) has multiple modalities in which cognition, emotion, and social changes are stimulated. The purpose of this study was to design a multimodal approach to a food art therapy (MM‐FAT) program and identify its effects on cognitive ability, daily living functioning, depression, self‐esteem, self‐efficacy, self‐expression, and social functioning in individuals with mild cognitive impairment (MCI) and mild dementia by employing a mixed methods research design. Methods The participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(32 citation statements)
references
References 48 publications
0
32
0
Order By: Relevance
“…22,23,[25][26][27][28] There was an overall positive trend with statistically significant improvement in four studies. 22,23,26,28 Sustained effect was found in two of those studies. 22,28 It was also noted that the measure of depression was consistent across all six studies, with the GDS utilised as the assessment tool.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…22,23,[25][26][27][28] There was an overall positive trend with statistically significant improvement in four studies. 22,23,26,28 Sustained effect was found in two of those studies. 22,28 It was also noted that the measure of depression was consistent across all six studies, with the GDS utilised as the assessment tool.…”
Section: Discussionmentioning
confidence: 88%
“…The included studies have identified some potential benefits, with improvements reported in cognition (five of seven studies [22][23][24][25][26] ), depressive symptoms (five of six studies 22,23,25,26,28 ) and levels of anxiety (three of three studies 23,25,28 ). However, the more important question of whether the identified benefits are sustained awaits future confirmation with only three studies performing follow up assessments over time following intervention completion.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations